Fixed investment, household consumption, and Economic growth: a structural vector error Correction model (svecm) study of Malaysia - Zulkefly Abdul, Karim; Bakri, Abdul Karim; Mohd Azlan, Shah Zaidi (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This paper examines the dynamic linkages between economic growth, fixed investment, and household consumption in Malaysia using a structural vector error correction model (SVECM) approach. The empirical results revealed that household consumption and fixed investment are significant in influencing the output growth in the short run. This finding tends to support the alternative view of growth hypothesis, namely fixed investment-led growth, and household consumption-led growth in the short run. In the long run, there is no significant effect of fixed investment and household consumption on growth. However, in the long run, there is a permanent effect of economic growth on household consumption and investment. This empirical finding implies that a demand side policy (for example through fiscal or monetary policy) which can affect the household consumption and investment is only effective to stimulate the economic activity in the short run. Thus a supply side policy would be needed to stimulate the economy in the long run.